The Role of Internal Supervision Unit in Enhancing Governance and Management of Higher Education - Husna Ni'matul Ulya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to complement research on themes in line with objects. It approaches that have never been found in the research to analyze the implementation of operational supervision budgeting in 2019 and 2020 based on the supervision result documents of the IAIN Ponorogo’s Internal supervision. The research approach uses qualitative implementation case studies with document analysis of supervision results conducted in pre-supervision and post-supervision. Primary and secondary data are collected from informants in the Internal Supervision Unit through interview data, observations, and documentation. The collected data were analyzed by Miles and Huberman's data analysis method and validity test by triangulation. The compliance of the implementation of activities in terms of the criteria for completeness of documents and budget management has yet to be maximized. Second, the effectiveness assessment with a goal and system approach by assessing aspects of inputs, processes, and outputs in internal supervision has been practical, while implementing activities could be more effective. Based on the analysis, the role of SPI as a supervisor has a role in the form of a) a supervisory role, b) a consultant role, and 3) a catalyst role.